Trinidad and Tobago : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, the economic developments and policy responses of Trinidad and Tobago after the crisis is reviewed. Policy recommendations are used to strengthen the legal and regulatory framework. According to the IMF's financial system stability assessment (FSSA), there were critical gaps in the overall legal, regulatory, and supervisory structure for the insurance sector. The quality of insurance sector supervision can be assessed against internationally accepted established 'core principles.' In this paper, an overview is presented of why the crisis occurred and some suggestions on how to prevent a future crisis.